Pengaruh Media Augmented Reality Terhadap Kemampuan Sains Anak Usia Dini - Meichika, Dhea; Yaswinda, Yaswinda (Universitas Islam Negeri Jurai Siwo Lampung, 2025)
This research is motivated by the low interest of children in science learning. This can be seen from the lack of children's attention to learning related to science, infrastructure and digital-based learning media are still minimally used, and the lack of variation in learning methods used by teachers. The purpose of this study was to determine the effect of the use of Augmented Reality media on the science abilities of early childhood. This study uses a quantitative approach with a quasi-experimental research type. The population of this study was all children of TK Pertiwi 1 Kantor Gubernur, with samples of class B4 as the experimental class and class B5 as the control class, each class consisting of 15 children. Data analysis techniques used normality tests, homogeneity tests, and hypothesis tests. Based on the hypothesis test table, it is known that the pre-test results obtained a sig value (2-tailed) of 0.340> 0.05. Thus, it can be concluded that there is no effect of Augmented Reality media on the science abilities of early childhood. While the results of the post-test hypothesis test obtained a sig value (2-tailed) of 0.030 <0.05. Thus, it can be concluded that there is an influence of Augmented Reality media on the science abilities of early childhood.